Sistema de Vigilancia Automatizada para el Control de Emergencias Domesticas en los Hogares del Cantón Babahoyo - Carbo Vera, Cristhian Orlando (2018)
Nowadays, the development of technology has helped us a lot in the development of different security and protection systems that have led most households, businesses and institutions of all kinds to have the need to have equipment that protects the welfare of the people. The lack of knowledge and the need to put an automated system of emergency control in homes and developed the prototype in order to care for and protect the life of the human being in their homes. That is why the system will have an emergency control including sensors for carbon dioxide leakage, flood sensor, motion sensors to detect individuals at night, temperature sensor, smoke sensor and humidity sensors. It must be borne in mind that the aforementioned sensors will go to homes placed in places that need greater security and protection since in the home the human life must be taken care of, where a project of quality, safety and efficiency will be built. With the passing of time in all parts of the world, millions of people have died from the respiration of carbon dioxide due to the great escape in homes, industries and public and private institutions that are harmful to the health of the human being. In homes nowadays due to global warming we have the high temperatures that cause problems in our health or material damages. There is a problem in some electronic devices today that are connected in homes that produce short circuits and cause damage to homes, producing a lot of smoke. Over the years, climate change and heavy rain have problems of humidity and flooding in people's homes, damaging the material assets of the home. Because of the lack of work there are people who dedicate themselves to damaging the property of another person by subtracting material things in order to sell it for their bad habits and thus destroying the welfare of others. That is why a prototype was developed, which seeks to reduce deaths from toxic gases, material damage to homes and prevent losses in homes, ensuring that the system complies with a solution to the aforementioned problems.